E-WoM: Pengaruhnya terhadap Keputusan Pembelian Tamu Restoran di Bandung Utara - Firdaus, Taufansyah; Abdullah, Taufik (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
The Development of information and technology has entered various elements of life, including human lifestyle when visiting restaurants. Some trends in the younger generation when visiting restaurants in Bandung, they often check in on social media, take selfie pictures with the interior design of the restaurant as the background, and the most common activity is taking photo of food or beverage products of the restaurant. furthermore, they upload the pictures to various social media. If referring to the literature, these activities could be classified as electronic word of mouth (e-WOM). The purpose of this study was to determine the role of e-word of mouth to increase the purchasing decision of restaurants in North Bandung. This is an explanatory study. The population in this study were restaurant’s customers in North Bandung so that the population was infinite. Thus the sampling technique used was quota sampling technique with a target of 100 respondents. The Data analysis technique used is multiple regression analysis. This research is expected to be an input for providers of food service business, particularly restaurants for consideration in conducting marketing activities in order to increase the sales of food and drink. The results of this research that there is a significant influence of the e-word of mouth on restaurant’s customers purchase decision in North Bandung.